2005
DOI: 10.1007/s11104-004-7611-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation in cotton, sorghum, and underlying soil as influenced by tillage, cover crops, and nitrogen fertilization

Abstract: Soil and crop management practices may influence biomass growth and yields of cotton (Gossypium hirsutum L.) and sorghum (Sorghum bicolor L.) and sequester significant amount of atmospheric CO 2 in plant biomass and underlying soil, thereby helping to mitigate the undesirable effects of global warming. This study examined the effects of three tillage practices [no-till (NT), strip till (ST), and chisel till (CT)], four cover crops [legume (hairy vetch) (Vicia villosa Roth), nonlegume (rye) (Secale cereale L), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
3
22
1
3
Order By: Relevance
“…This is in the upper part of the range of observed C sequestration rates in humid regions. In the USA, the incorporation of hairy vetch as green manure in cereal, cotton and vegetable production resulted in a wide range of SOC accumulation of 0.2 to 2.7 t ha −1 yr −1 in topsoils (0 to 30 cm) in the first 3 to 7 years of the experiments (Sainju et al, 2002(Sainju et al, , 2003(Sainju et al, , 2005b. In Japan, C sequestration ranges from 0.6 to 1.0 t ha −1 yr −1 were found in topsoils (0 to 30 cm) by including hairy vetch as cover crop in rice and soybean cultivation under a humid subtropical climate (Higashi et al, 2014).…”
Section: Increase Of Soc and Carbon Sequestration Potentialmentioning
confidence: 99%
“…This is in the upper part of the range of observed C sequestration rates in humid regions. In the USA, the incorporation of hairy vetch as green manure in cereal, cotton and vegetable production resulted in a wide range of SOC accumulation of 0.2 to 2.7 t ha −1 yr −1 in topsoils (0 to 30 cm) in the first 3 to 7 years of the experiments (Sainju et al, 2002(Sainju et al, , 2003(Sainju et al, , 2005b. In Japan, C sequestration ranges from 0.6 to 1.0 t ha −1 yr −1 were found in topsoils (0 to 30 cm) by including hairy vetch as cover crop in rice and soybean cultivation under a humid subtropical climate (Higashi et al, 2014).…”
Section: Increase Of Soc and Carbon Sequestration Potentialmentioning
confidence: 99%
“…Additionally, it is unique as an actively researched bioenergy feedstock, because it is grown as an annual crop, thus the entire root system is left to decompose every year. Sorghum root biomass estimates range from ~ 0.5 to 6.1 mg dry matter per ha based on field measurements, to 7 mg dry matter per ha based on modeled projections (Meki, Snider, Kiniry, Raper, & Rocateli, ; Monti & Zatta, ; Sainju, Whitehead, & Singh, ; Schittenhelm & Schroetter, ).…”
Section: Introductionmentioning
confidence: 99%
“…Johnston et al [65] reported that application of nitrogen fertilizer increases sorghum culm yield. Sainju et al [66] and Almodares et al [67] reported an increase of biomass production due to nitrogen fertilization. The mycorrhization of plants did not promote significant biomass differences from the unfertilized control treatment in either trial year, whereas in the second year, the mycorrhizal fungi effect was also not statistically different from N fertilized plants (Table 5).…”
Section: Plant Aboveground Dry Biomass and Its Componentsmentioning
confidence: 98%